Factors Affecting Innovative Work Behavior in Pharmaceutical Companies: The Role of Human Capital, Social Capital, Knowledge Sharing, and Creativity - Dhaneswara, Cintya Astari; Pusparini, Elok Savitri (Jurnal Manajemen Bisnis, 2023)
This study aims to analyze the influence of human capital, social capital, knowledge sharing, and creativity on employees' innovative work behavior. Data collection was conducted using an online questionnaire with 302 respondents in a pharmaceutical company in Indonesia and the data were analyzed using the structural equation modeling (SEM) method with SPSS Amos software version 24. The results of the study stated that human capital has a positive and significant effect on social capital, which in turn has a positive and significant effect on knowledge sharing, and then has a positive and significant effect on creativity. As expected, creativity has a positive and significant effect on innovative work behavior. As a mediating variable, knowledge sharing mediates the relationship between social capital and creativity, and creativity mediates the relationship between knowledge sharing and innovative work behavior. Human capital does not show a significant direct effect on knowledge sharing, however, social capital mediates the relationship between human capital and knowledge sharing.